Factors affecting Bangladeshi high school students' practices of sanitation and hygiene - Saha, Bithe; Hoque, Majedul; Avi, Anupam Sarker; Das, Asim (International Journal of Public Health Excellence (IJPHE), 2024)
Background: Better sanitation and hygiene standards are beneficial for preventing infections, limiting the spread of pathogens, and fostering overall health in educational environments. On the other hand, not much is known about school-student's hygiene and sanitation habits. The purpose of this study is to identify and comprehend the variables that affect students' behavior related to sanitation and hygiene in classrooms. Method: This study was carried out at the Katiadi Government High School, a high school in a Bangladeshi upazilla town. An exploratory qualitative study design, based on the Integrated Behavioral Model for Water, Sanitation, and Hygiene (IBM-WASH) was used. Before utilizing them, the effectiveness and clarity of the semi-structured interview guides were tested, which included questions about behavior, access, and practices related to sanitation and hygiene. Result: The students had quite low sanitation and hygiene practices despite having a reasonable level of awareness and knowledge. Sanitation and hygiene practices were influenced by a wide range of interrelated factors, which also affected one another. Contextual factors (lack of upkeep and cleanliness, availability of sanitary products), socio-behavioral factors (norms, peer influence), and individual factors (gender awareness, perception, and sense of health benefits). Conclusion: To advance improved sanitation and hygiene practices among school students, multi-level interventions such as regular delivery of WASH-related materials and agents, promotion of low-cost WASH interventions, quality cleaning services improvement, close observation of cleaning activities, individual hygiene behavior promotion, and introduction of gender-sensitive WASH infrastructure and construction may be helpful.